Whistleblowing: An integrative literature review of data-based studies involving nurses - Jackson, D.; Hickman, L.; Hutchinson, M.; Andrew, S.; Smith, James; Potgieter, I.; Cleary, M.; Peters, K. (eContent Management, 2014)
To summarise and critique the research literature about whistleblowing and nurses. Background: Whistleblowing is identified as a crucial issue in maintenance of healthcare standards and nurses are frequently involved in whistleblowing events. Despite the importance of this issue, to our knowledge an evaluation of this body of the databased literature has not been undertaken. Method: An integrative literature review approach was used to summarise and critique the research literature. A comprehensive search of five databases including Medline, CINAHL, PubMed and Health Science: Nursing/Academic Edition, and Google, were searched using terms including: 'Whistleblow*,' 'nurs*.' In addition, relevant journals were examined, as well as reference lists of retrieved papers. Papers published during the years 2007-2013 were selected for inclusion. Findings: Fifteen papers were identified, capturing data from nurses in seven countries. The findings in this review demonstrate a growing body of research for the nursing profession at large to engage and respond appropriately to issues involving suboptimal patient care or organisational wrongdoing. Conclusions: Nursing plays a key role in maintaining practice standards and in reporting care that is unacceptable although the repercussions to nurses who raise concerns are insupportable. Overall, whistleblowing and how it influences the individual, their family, work colleagues, nursing practice and policy overall, requires further national and international.